The Birth of a New Nordic Career Guidance Journal - Fredrik Hertzberg; Jaana Kettunen; Sif Einarsdottir; Erik Hagaseth Haug; Rie Thomsen (Nordic Journal of Transitions, Careers and Guidance)
Welcome to the first issue of the Nordic Journal of Transitions, Careers and Guidance (NJTCG), a new international forum for the growing body of research in the Nordic region. Resumé Velkommen til første udgave af Nordic Journal of Transitions, Careers and Guidance (NJTCG), et nyt internationalt forum for en stødt stigende publicering af forskning om indenfor overgange, karriere og vejledning i Norden. Abstrakti Nordic Journal of Transitions, Careers and Guidance (NJTCG) on uusi kansainvälinen julkaisufoorumi kasvavalle pohjoismaiselle ohjausalan tutkimukselle. Tervetuloa ensimmäisen numeron pariin. Útdráttur Velkomin, og takk fyrir innlitið í fyrsta hefti Nordic Journal of Transitions, Careers and Guidance (NJTCG), sem er alþjóðlegur vettvangur fyrir rannsóknir í náms- og starfsráðgjöf á Norðurlöndunum. Abstrakt Velkommen til første utgave av Nordic Journal of Transitions, Careers and Guidance (NJTCG), et nytt internasjonalt forum for det økende omfanget av forskning i Norden. Abstrakt Välkomna till det första numret av Nordic Journal of Transitions, Careers and Guidance (NJTCG), ett nytt internationellt forum för nordisk forskning om övergångar, karriärer och vägledning – ett snabbt växande forskningsfält.